Pharmacy Students' Perceptions and Emotional Responses to Aggressive Incidents in Pharmacy Practice - Rahim, Hamid (American Journal of Pharmaceutical Education, 2010)
OBJECTIVE: To explore pharmacy students' experiences with and perceptions of aggressive incidents in pharmacy practice. METHODS: Data were taken from a survey completed by second-year pharmacy (P2) students and analyzed using a retrospective, cross-sectional design. Survey items were adapted using the following scales: Perception of Aggression Survey (POAS), List of Aggressive Incidents experienced by mental health staff, and List of Emotions experienced by nurses. RESULTS: The majority of respondents did not identify aggression as normal, instead perceiving it as a violent reaction and functional. The 3 most frequent aggressive incidents experienced were: verbal abuse to face (40%); verbal abuse on the phone (39%); and refusal to cooperate with instructions (34%). The 3 most frequent emotions reported were: frustration (70%), empathy (65%), and no pride in their profession (70% rarely-never). CONCLUSION: Pharmacy students reported experiencing aggressive incidents with patients in person and on the phone, and with patients not following instructions. Preparing future pharmacists in techniques to address and resolve patients' aggression must become a priority for pharmacy academia and further research in this area is needed.